REVIEW. VULNERABILITY AND DEMOCRACY IN IBERO-AMERICA (Journal of the Spanish Institute for Strategic Studies, 2018)
VULNERABILITY AND DEMOCRACYIN IBERO-AMERICAAuthors: Federico Aznar and Marisa Ramos. Publisher: Tirant lo Blanch,Monografías collection, 2015, 372 pages.ISBN: 978-8490867792